Analysis Of The Influence Of Role, Performance, Transparency, And Compliance Of Village Officials On The Management Of Village Funds In Villages In Pancur Batu Sub-District, Deli Serdang District - Lamria Sagala; Farida Sagala; Mitha Christina Ginting; Gracesiela Y Simanjuntak; Rike Yolanda Panjaitan (Jurnal Ilmiah Accusi, 2025)
This research aims to determine the influence of role, performance, transparency and compliance of village officials on village fund management in Pancur Batu District, Deli Serdang Regency. This type of research is quantitative research using primary data. The population in this study was all village officials in villages in Pancur Batu District with a census sample of 73 respondents. The data analysis technique used in this research is descriptive statistics. Researchers carried out primary data quality tests by conducting validity and reliability tests, classical assumption tests, multiple linear regression tests and hypothesis tests using the SPSS 25 application. The results of this research individually show that the role of Village Officials has a positive and significant influence on Village Fund Management. The performance of Village Officials has a positive and significant effect on Village Fund Management. Transparency has a positive and significant effect on Village Fund Management. Compliance has a positive and significant effect on Village Fund Management. Simultaneously, the Role, Performance, Transparency and Compliance of Village Officials have a positive and significant effect on Village Fund Management. In the coefficient of determination test, data results were obtained at 63,4% which could be explained by independent variables, namely the role of village officials, performance of village officials, transparency and compliance with village officials. Meanwhile, the remaining 36,6% is explained by other variables not included in this research model